Evaluation of a mechanistic model of potassium uptake by cotton in vermiculitic soil - Brouder, S.M.; Cassman, K.G. (Wiley, 1994)
The Cushman‐Barber model was evaluated for K uptake by cotton (Gossypium hirsutum L.) from vermiculitic soils of high K‐fixation capacity and low solution‐phase K+ concentration. On these soils, cotton exhibits late‐season K deficiency while other crop species remain unaffected. Four soil treatments of NH4‐N, K, or both were combined factorially in a vertically split‐pot system to create eight plant treatments of different uniform and nonuniform soil nutrient environments. Depending on the treatment, initial model output produced both substantial under‐ and overpredictions of whole‐plant K accumulation. Model precision was greatly improved by changing the Michaelis‐Menten kinetic parameters for uptake at the root surface to reflect differences in shoot K/N balance, a more accurate measure of plant K demand in the presence of variable soil N supply. Regression revealed a linear relationship between the predicted and the observed K uptake (r2 = 0.87) but, across treatments, the model underpredicted accumulation by 43%. Model predictions were further improved by estimating soil buffer capacity from a Langmuir fit of a K adsorption isotherm rather than from the relationship between exchangeable solid‐phase and solution‐phase K pools. Sensitivity analyses were performed to identify key determinants of cotton K acquisition from vermiculitic soils of high K‐fixation capacity. The analyses demonstrated that both Michaelis‐Menten kinetic and soil supply parameters were strong determinants of K uptake on these soils and thus warrant more emphasis than previously suggested by model validations conducted on soils with greater K supply and less K‐fixation capacity.